SPECIAL FEATURES OF RECOMBINATIONS AND MUTATIONS OF THE NOSOCOMIAL PATHOGENS IN GENERAL HOSPITALS - Solomennyi, A.P.; Zubareva, N.A. (Perm Federal Research Centre Journal, 2014)
For the purpose of improving the molecular methods of revealing and monitoring the bacterial pathogens of nosocomial infections the paper substantiates the necessity of in-depth studies of integrons – genetic elements of multi-drug resistance (by the example of large teaching hospitals of Perm and St.-Petersburg). It is demonstrated that in Perm the integron-positive isolates carrying class 1 integrons are prevailing in the structure of Acinetobacter baumannii . In total, during the reporting period (2010–2012) the proportion of these isolates comprised 77 % (72 prospective isolates were analyzed). Perm carbapenem-resistant strain 60 (global epidemic type II) was chosen as the object for the first (in national practice) sequencing of complete genome of the pathogenic Acinetobacter .A method of genotypic «sorting» of hospital strains using duplex PCR is suggested for practical application on the basis of clinical laboratories of hospitals providing high-technology medical care. In addition, optimal PCR mode has been selected to determine the gene of unique metallo-beta- lactamase NDM (New Delhi) and concurrently the integron-specific sequences in the super-resistant strains.